S123 Coronary atherosclerosis detected at elective angiography is more severe in people with COPD than in those without. (12th November 2015) - Ruickbie, SV; Prasad, A; Jones, PW; Baker, EH
Abstract : Introduction: Coronary artery disease (CAD) affects 16–53% people with chronic obstructive pulmonary disease (COPD) and is the cause of death in 25% (Smith and Wrobel. Int J COPD. 2014;9:871–888). People with COPD have both high prevalence of cardiovascular risk factors and increased systemic inflammation and oxidative stress that can drive atherosclerosis. We therefore tested the hypothesis that patients with COPD have more extensive coronary artery disease compared to those without. Methods: All patients attending for elective coronary angiography March–July 2015 were invited to take part in a cross-sectional, observational study. Participants who gave consent underwent clinical assessment and spirometry prior to the procedure. COPD was defined as FEV1 /FVC 10 pack-year smoking history. CAD burden was quantified from the angiogram using the Gensini score (Neeland et al . Am Heart J 2012;164:547–552). A single rater (Professor of Interventional Cardiology), blinded to clinical diagnosis, determined number and severity of lesions. Blinded repeats were performed and ratings compared to clinical reports to ensure reliability. A nonlinear score was assigned to each lesion based on severity of stenosis and a multiplier applied depending on lesion location in the coronary tree. Lesion scores were summed to derive Gensini score which was log-transformed for analysis. Results: 249 of 294 (85%) people approached took part, 46 (19%) had COPD. The Table 1 compares demographic, respiratory disease-related and cardiovascular risk factors between people with and without COPD. Gensini score was higher in COPD patients (22.5 (8.5–46.0)) than in those without (12.5 (6.0–26.8), p = 0.04), indicating greater burden of coronary atheroma. COPD patients had more circumflex lesions and tended to have more lesions in the right coronary artery and in total than those without. Conclusions: People with COPD have more severe coronary artery disease than those without. This analysis cannot determine whether this was due to the presence of COPD or the fact that patients with CAD and COPD had much greater cigarette smoke exposure than CAD patients without COPD.